Pirtobrutinib in relapsed or refractory B-cell malignancies (BRUIN): a phase 1/2 study. Issue 10277 (6th March 2021) - Mato, Anthony R; Shah, Nirav N; Jurczak, Wojciech; Cheah, Chan Y; Pagel, John M; Woyach, Jennifer A; Fakhri, Bita; Eyre, Toby A; Lamanna, Nicole; Patel, Manish R; Alencar, Alvaro; Lech-Maranda, Ewa; et al.
Summary: Background: Covalent Bruton's tyrosine kinase (BTK) inhibitors are efficacious in multiple B-cell malignancies, but patients discontinue these agents due to resistance and intolerance. We evaluated the safety and efficacy of pirtobrutinib (working name; formerly known as LOXO-305), a highly selective, reversible BTK inhibitor, in these patients. Methods: Patients with previously treated B-cell malignancies were enrolled in a first-in-human, multicentre, open-label, phase 1/2 trial of the BTK inhibitor pirtobrutinib. The primary endpoint was the maximum tolerated dose (phase 1) and overall response rate (ORR; phase 2). This trial is registered with ClinicalTrials.gov, NCT03740529 . Findings: 323 patients were treated with pirtobrutinib across seven dose levels (25 mg, 50 mg, 100 mg, 150 mg, 200 mg, 250 mg, and 300 mg once per day) with linear dose-proportional exposures. No dose-limiting toxicities were observed and the maximum tolerated dose was not reached. The recommended phase 2 dose was 200 mg daily. Adverse events in at least 10% of 323 patients were fatigue (65 [20%]), diarrhoea (55 [17%]), and contusion (42 [13%]). The most common adverse event of grade 3 or higher was neutropenia (32 [10%]). There was no correlation between pirtobrutinib exposure and the frequency of grade 3 treatment-related adverse events. Grade 3 atrial fibrillation or flutter was not observed, and grade 3 haemorrhage was observed in one patient in the setting of mechanical trauma. Five (1%) patients discontinued treatment due to a treatment-related adverse event. In 121 efficacy evaluable patients with chronic lymphocytic leukaemia (CLL) or small lymphocytic lymphoma (SLL) treated with a previous covalent BTK inhibitor (median previous lines of treatment 4), the ORR with pirtobrutinib was 62% (95% CI 53–71). The ORR was similar in CLL patients with previous covalent BTK inhibitor resistance (53 [67%] of 79), covalent BTK inhibitor intolerance (22 [52%] of 42), BTK C481-mutant (17 [71%] of 24) and BTK wild-type (43 [66%] of 65) disease. In 52 efficacy evaluable patients with mantle cell lymphoma (MCL) previously treated with covalent BTK inhibitors, the ORR was 52% (95% CI 38–66). Of 117 patients with CLL, SLL, or MCL who responded, all but eight remain progression-free to date. Interpretation: Pirtobrutinib was safe and active in multiple B-cell malignancies, including patients previously treated with covalent BTK inhibitors. Pirtobrutinib might address a growing unmet need for alternative therapies for these patients. Funding: Loxo Oncology.